Приватне право: ціннісні аспекти формування концепту - Харитонов, Євген Олегович; Kharytonov, Yevhen Olehovych; Kharytonov, Yevhen; Харитонова, Олена Іванівна; Kharytonova, Olena; Kharytonova, Olena Ivanivna (ВД "Гельветика", 2019)
У статті розглядається вплив суспільних цінностей на формування концепту приватного права. На підґрунті розуміння цінностей як імперативів, норм та ідеалів для людської думки, людської дії й соціально-історичної творчості стверджується, що «римське право» мало основою такі ціннісні категорії, як «справедливість», «добра совість», «добра воля», «громадська честь», «доблесть», «порядність». Доводиться, що уявлення римського суспільства про справедливість, добро та зло, інші цінності сформовані під впливом етичних положень давньогрецької філософії, сприйнятих потім римською ментальністю.

The article analyzes the influence of social values on the formation of the concept of private law. Based on the understanding of values as imperatives, norms and ideals for human thought, human action and socio-historical creativity, it is stated that “Roman law”, as the embodiment of real and existing laws of natural law, became the basis of modern law in Europe. Derived from Roman law, the concept of “Roman private law” is the basis for the formation of the modern concept of private law. The maxim of Ulpianus is analyzed, according to which the notion “right” (jus) derives its name from the word “justitia”, since “ right is the science of good and justice” (A.1.1). It is proved that the term “justitia” should not be translated as “jurisdiction”, but as “justice”, thus linking it directly with basic civilizational values. It is the latter that corresponds to the concept of law in ancient Rome, where in the period of the Republic and Principate such value categories as “justice”, “good conscience”, “good will”, “public honor”, “valor”, “decency” became extremely important. Although in everyday life not all the inhabitants of Rome adhered to these principles, these concepts were social values for the Romans and should be considered in that sense. It is proved that the ideas of justice, good and evil, other values of the Roman society, were formed under the influence of the ethical principles of ancient Greek philosophy, later adopted by the Roman mentality. Analysis of the Stoic and Epicurean doctrine of the formation of the value basis of Roman law gave grounds for the conclusion that the Stoics’ views served to a greater extent the basis of public law, as they related to the problems of relations between a citizen and society (state), problems of power, governance, etc. Later they could be interesting from the point of view of the right of a private person. On the other hand, the Epicureans considered the problems of society, going to them from the needs, attitudes, and the will of certain individuals. That is, it was private rights that were recognized as defining here. Therefore, the influence of the Epicurean views on the establishment of the foundations of private law should have been more significant. At the same time, it is emphasized that the stoic and epicurean vision of the world in ancient Rome, in defining the values that served as the basis for the formation of law, are not opposed, but complementary.
Харитонов Є. О. Приватне право: ціннісні аспекти формування концепту / Є. О. Харитонов, О. І. Харитонова // Часопис цивілістики : наук.-практ. журн. / редкол.: С. В. Ківалов (голов. ред.), Є. О. Харитонов (заст. голов. ред.), К. Г. Некіт (відп. секр.) [та ін.]. – Одеса : Гельветика, 2019. – Вип. 33. – С. 6-11.
Keywords: Research Subject Categories::LAW/JURISPRUDENCE; приватне право; цінності; концепт; римське право; стоїцизм; епікурейство; private law; values; concept; Roman law; stoicism; epicureanism